Prognostic value of mismatch repair protein expression in unresectable gastric cancer - Nguyen, Thi Hong Chuyen; Nguyen, Thi Thu Giang; Nguyen, Tran Bao Song; Ngo, Quy Tran; Dang, Cong Thuan (Tạp chí Y Dược Huế, 2024)
Background: Gastric cancer (GC) is one of the common types of cancer in Vietnam. Over 50% of GCs are diagnosed at an unresectable stage. Deficiency in mismatch repair proteins (MMR) leading to microsatellite instability (MSI-H) is a crucial prognostic factor currently under investigation in these patients. Therefore, this study aimed to determine the rate of MMR protein expression and its correlation with clinical characteristics, histopathological features, and overall survival in unresectable GC patients. Materials and methods: A descriptive case series study on 83 GC patients at unresectable stage, treated at Hue University of Medicine and Pharmacy Hospital and Hue Central Hospital from June 2020 to December 2022. Immunohistochemical staining was utilized to assess MMR protein expression. A deficiency in any MMR protein was considered as deficient mismatch repair proteins (dMMR). Conversely, the expression of all four MMR proteins in tumor cells was defined as proficient mismatch repair proteins (pMMR). Result: The dMMR rate was 10.8% and correlated with tumor size > 5 cm (p = 0.026) and well-differentiated tumors (p = 0.012). There was no association between MMR protein expression and tumor location, lymph node metastasis, or histological subtype. The dMMR group showed a significantly improved overall survival compared to the pMMR group, with a median overall survival of 19.1 ± 1.8 months compared to 9.3 ± 0.8 months (p = 0.02). Conclusions: There are correlation between MMR protein deficiency and tumor size and differentiation. dMMR GC patients have a better prognosis compared to those with pMMR